Atherosclerotic Autoantigen ALDH4A1 as a Novel Immunological Indicator for Plaque Erosion in Patients with ST Segment Elevated Myocardial Infarction - Li, Jiannan; Chen, Runzhen; Zhou, Jinying; Wang, Ying; Zhao, Xiaoxiao; Liu, Chen; Zhou, Peng; Chen, Yi; Song, Li; Li, Nan; Yan, Hongbing; Zhao, Hanjun (Thrombosis and Haemostasis, 2023)
Objective Aldehyde dehydrogenase 4A1 (ALDH4A1) was recently reported to be a novel autoantigen of atherosclerosis. However, its role in different phenotypes of acute coronary syndrome remains unclear. Herein, we planned to explore the circulating and regional expression of ALDH4A1 in patients with plaque rupture (PR) and plaque erosion (PE) determined by optical coherence tomography (OCT).Methods and Results After applying the inclusion and exclusion criteria, a prospective series of 312 patients with ST segment elevated myocardial infarction (STEMI), including 161 patients with PR and 151 patients with PE determined by OCT, were enrolled for plasma ALDH4A1 testing. In addition, ALDH4A1 was quantified using immunofluorescence in aspirated coronary thrombus samples obtained from 31 patients with PR and 25 patients with PE. In addition, we established an atherosclerosis mouse model and analyzed the distribution of ALDH4A1 expression in different mouse organs. Furthermore, we compared the level of ALDH4A1 in the spleen and carotid artery between Apoe−/− and C57 mice. The results showed that the plasma level of ALDH4A1 was significantly higher in STEMI patients with PE than in those with PR (4.6 ng/mL [2.2–8.7] vs. 3.5 ng/mL [1.6–5.6] p = 0.005). The expression of ALDH4A1 in aspirated coronary thrombi was also significantly higher in patients with PE than in those with PR (mean gray value: 32.0 [23.6–40.6] vs. 16.8 [14.0–24.5], p < 0.001). In animal models, the expression of ALDH4A1 is much higher in the spleen than in other organs, and the level of ALDH4A1 is significantly elevated in the spleen and carotid artery of Apoe−/− mice compared with C57 mice.Conclusion The high levels of ALDH4A1 in the plasma and aspirated coronary thrombi independently correlated with PE in patients with STEMI. These results suggested that ALDH4A1 is involved in the mechanism of PE and serves as a promising biomarker and treatment target for patients with PE.
Keywords: aldehyde dehydrogenase 4A1; plaque erosion; biomarker